Spirals from the sea an anthropological look at shells - Safer, Jane Fearer; Gill, Frances McLaughlin; Binns, Betty (New York, New York Clarson N. Potter, Inc., 1982)
Contains many color and black & white plates showing the use of shells in costume and ritual throughout the tribal world.
Shells in daily life -- Shells as wealth -- Shells as emblems of status -- Shells in ritual and myth.
"Published in association with the American Museum of Natural History."
Includes bibliographical references and index.
Keywords: Shells -- Social aspects; Shellcraft